The perceptions’ study of ACIS Part 5 UiTM Puncak Alam students towards gold investment / Noor Nafisah Ishak - Ishak, Noor Nafisah (2019)
Gold is often known as a commodity but it was more like a currency. Gold investment is one of Malaysia's popular investment as it retains its value during the recession's inflationary period. This research is intended to analyze the perceptions’ of the students toward gold investment. In particular, the researcher would like to know if the students have the right perception of gold investment and the knowledge about gold investment which is complies with the Islamic principle. To answer this question, researcher used questionnaire as a method. The questionnaire will be given to students Academy of Contemporary Islamic Studies in Diploma Muamalat Part 5 at UiTM Puncak Alam. Three questions are created to achieve the objective of the study which are the knowledge of gold investment. Second, the advantages of gold investment. Third, the rules of gold investment in Islamic law. The findings support the common perception that direct and indirect investment in gold can be a beneficial investment as most of the respondents know about the gold investment. However, some of the respondents still lack of knowledge about the the rules and the advantages of gold investment. Based on the result a several recommendation can be implement by the future researcher which is they should expose more to the respondents about how gold investment brings benefits for their future.